Analisis Uji Lentur Beton SCC Dengan Menggunakan Pasir Cilopang - Dendi Yogaswara; Virdi Muhamad (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Self-compacting concrete (SCC) is self-flowing concrete that can be printed on formwork with very little or no compaction. One of them is by adding admixture superplasticizer. The purpose of this research is to determine the effect of superplasticizer admixture with various variations on flexural strength. The method used in this research is the experiment of adding superplasticizer admixture to the concrete mixture with variations of 3%, 4% and 5%. The sample was made of 3 test objects in the form of blocks with dimensions of 15 cm x 20 cm x 100 cm for a design value of 15 MPa. Based on the results of the flexural strength test of concrete beams after 28 days of flexural strength testing, the highest yield was obtained in the second sample of 4% mixture with a maximum P load of 32.2 KN after converting to 18.22 MPa. Whereas for the 1st sample it was a 3% mixture with a maximum P load of 22 KN after converting to 12.44 MPa and for the 3rd sample it was a 5% mixture with a maximum P load of 22.9 KN after converting it to 12.95 MPa. 3. It was found that the average of the 3 samples was 14.54 MPa, a little more to exceed the target of 15 MPa.